Sistem Monitoring Dan Kontroling Irigasi Sawah Menggunakan Microcontroller Wemos D1 Berbasis Internet Of Things - Supriyanto Supriyanto; Eka Satria Wibawa (Elkom : Jurnal Elektronika dan Komputer, 2020)
Irrigation is a land irrigation system by damming water sources. Irrigation as the provision, regulation and disposal of water to support agricultural needs. Irrigation is generally used by farmers, especially farmers in rice fields to irrigate and provide water supply to agricultural land, monitoring water stock in rice fields must be done frequently because rice water needs must be balanced with a lack of water supply or excess water supply in rice fields is not good for rice growth . So far, farmers have monitored irrigation channels manually, the location of the rice fields from the farmer's house often causes rice plants to experience scarcity because the floodgates are not opened when the water supply is running low or experiencing water supply. excess because the floodgates are opened for too long, this will greatly disturb the growth of rice plants. Making a monitoring and control system for irrigation channels using a water level sensor installed on the ESP 8266 microcontroller (Wemos D1), the system uses a programming language c. This tool can be used to open the irrigation door if the water supply in the rice fields is below the minimum limit and will close the water gate when the water supply has reached the maximum limit, the servo motor is used to open and close the floodgates. . . The monitoring results obtained will be displayed to users in real time through the android application interface and will be stored in the form of a text file on the storage media.